Analisis Penerapan Produk Digital, Brand Awareness, dan Kualitas Layanan terhadap Persepsi Kinerja Cabang Bank X di Semarang - Metta, Wimala Marsela; Susilo, Bambang Widjanarko; Sulartopo, Sulartopo; Febryantahanuji, Febryantahanuji; Kholifah, Siti (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study aims to analyse the influence of digital products, brand awareness, and service quality on perceived branch performance in a financial institution in Indonesia. The research is motivated by the accelerating digital transformation in the country’s banking industry, which requires conventional financial institutions to innovate to remain competitive amid the growth of fintech and digital banks. The main problem addressed is how these three variables simultaneously and partially affect perceived branch performance. A quantitative approach was employed using survey techniques and questionnaires distributed to customers. Multiple linear regression analysis was used to process the data. The results reveal that digital products, brand awareness, and service quality significantly influence perceived branch performance, both individually and collectively. The coefficient of determination (R²) is 0.652, indicating that the three variables can explain 65.2% of the variance in perceived branch performance. These findings highlight the importance of integrating digital innovation, strong brand presence, and excellent service in improving competitiveness and branch performance in the digital era. The study contributes practical implications for financial institutions in formulating strategic improvements to maintain relevance and competitiveness amid digital disruption.